Catabolism and interactions of syntrophic propionate- and acetate oxidizing microorganisms under mesophilic, high-ammonia conditions - Weng, Nils; Singh, Abhijeet; Ohlsson, Jonas A.; Dolfing, Jan; Westerholm, Maria (Frontiers in Microbiology, 2024)
Microbial inhibition by high ammonia concentrations is a recurring problem that significantly restricts methane formation from intermediate acids, i.e. propionate and acetate, during anaerobic digestion of protein-rich waste material. Studying the syntrophic communities that perform acid conversion is challenging, due to their relatively low abundance within the microbial communities typically found in biogas processes and disruption of their cooperative behavior in pure cultures. To overcome these limitations, this study examined growth parameters and microbial community dynamics of highly enriched mesophilic and ammonia-tolerant syntrophic propionate and acetate-oxidizing communities and analyzed their metabolic activity and cooperative behavior using metagenomic and metatranscriptomic approaches. Cultivation in batch set-up demonstrated biphasic utilization of propionate, wherein acetate accumulated and underwent oxidation before complete degradation of propionate. Three key species for syntrophic acid degradation were inferred from genomic sequence information and gene expression: a syntrophic propionate-oxidizing bacterium (SPOB) ‘Candidatus Syntrophopropionicum ammoniitolerans’, a syntrophic acetate-oxidizing bacterium (SAOB) Syntrophaceticus schinkii and a novel hydrogenotrophic methanogen, for which we propose the provisional name ‘Candidatus Methanoculleus ammoniitolerans’. The results revealed consistent transcriptional profiles of the SAOB and the methanogen both during propionate and acetate oxidation, regardless of the presence of an active propionate oxidizer. Gene expression indicated versatile capabilities of the two syntrophic bacteria, utilizing both molecular hydrogen and formate as an outlet for reducing equivalents formed during acid oxidation, while conserving energy through build-up of sodium/proton motive force. The methanogen used hydrogen and formate as electron sources. Furthermore, results of the present study provided a framework for future research into ammonia tolerance, mobility, aggregate formation and interspecies cooperation.